2017
DOI: 10.2147/opth.s125676
|View full text |Cite
|
Sign up to set email alerts
|

Switching to aflibercept among patients with treatment-resistant neovascular age-related macular degeneration: a systematic review with meta-analysis

Abstract: PurposeTo systematically review anatomical and functional outcomes subsequent to switching from bevacizumab/ranibizumab to aflibercept monotherapy in patients with treatment-resistant neovascular age-related macular degeneration (nAMD).DesignSystematic review and meta-analysis.MethodsMedline, PubMed, Embase, and Cochrane databases were searched up to July 2016 for available scientific literature which met inclusion criteria. Eligible studies reported visual and anatomical outcomes with at least 6 months of fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 62 publications
2
32
1
5
Order By: Relevance
“…The findings reported here are remarkably similar to the overall results of uncontrolled switching trials summarized in 2 meta-analyses. 9,13 Spooner et al 13 reported mean 1.11-and 0.63-letter gains at months 6 and 12, respectively, after switching from ranibizumab or bevacizumab to aflibercept. Neither change was significantly different from a 0-letter gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings reported here are remarkably similar to the overall results of uncontrolled switching trials summarized in 2 meta-analyses. 9,13 Spooner et al 13 reported mean 1.11-and 0.63-letter gains at months 6 and 12, respectively, after switching from ranibizumab or bevacizumab to aflibercept. Neither change was significantly different from a 0-letter gain.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses examining numerous anti-VEGF switching studies have shown that most patients with nAMD who switch treatment from either ranibizumab or off-label bevacizumab to aflibercept demonstrate continued anatomic improvement with vision stabilization or limited visual improvement. 9,13 Although these benefits generally are attributed to the new anti-VEGF agent, limitations in study design preclude definitive conclusions regarding the cause of the improvement. Most of these studies do not include a comparator arm, and as a result, it is unclear if the benefits achieved are the result of the new anti-VEGF drug, the result of continuing anti-VEGF treatment for a longer duration, or something else.…”
mentioning
confidence: 99%
“…; Spooner et al. ). Few have assessed the efficacy for refractory cases of macular oedema in RVO (Konidaris et al.…”
Section: Introductionmentioning
confidence: 97%
“…It is possible that some eyes may respond better to one VEGF inhibitor than another, however few prospective studies have evaluated the effects of switching VEGF inhibitors in eyes with RVO . Switching studies have been reported in age related macular degeneration and diabetic macular oedema . However, there are few published prospective studies which examine the efficacy of switching anti‐VEGF agents in eyes with RVO …”
Section: Introductionmentioning
confidence: 99%